Micro-Glocal Project on Age-Related Issues at ‘‘Ramon Pando Ferrer’’ Elementary School - Fernández Jaramillo, Lázaro Michel (Universidad Central "Marta Abreu" de Las Villas. Facultad de Educación Media.Departamento de Lenguas Extranjeras, 2020)
This research was conducted to Elementary Education students with the purpose of enhancing Citizenship Education, and to contribute promoting awareness mainly about age-related issues. After the implementation of some empirical methods like: survey, interview, analysis of documents and participant observation; this research reveals that elementary students lack knowledge, attitudes, acting ways and sensitiveness to the elderly. These research deeps into the theoretical and methodological background on the topic and it offers outstanding information regarding age-related issues connecting global and local perspectives. The final scientific result was gathered in a system of extracurricular activities by using storytelling and short stories through the teaching learning process of English in such a way to promote young learners’ awareness on age-related issues as to be better citizens ready to face the challenges of the 21st century.
Keywords: Educación; Educación Superior; Didáctica del Inglés; Enseñanza de la Lenguas Extranjeras